2016
DOI: 10.5194/gmd-9-2471-2016
|View full text |Cite
|
Sign up to set email alerts
|

Experimental design for three interrelated marine ice sheet and ocean model intercomparison projects: MISMIP v. 3 (MISMIP +), ISOMIP v. 2 (ISOMIP +) and MISOMIP v. 1 (MISOMIP1)

Abstract: Abstract. Coupled ice sheet–ocean models capable of simulating moving grounding lines are just becoming available. Such models have a broad range of potential applications in studying the dynamics of marine ice sheets and tidewater glaciers, from process studies to future projections of ice mass loss and sea level rise. The Marine Ice Sheet–Ocean Model Intercomparison Project (MISOMIP) is a community effort aimed at designing and coordinating a series of model intercomparison projects (MIPs) for model evaluati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
274
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 158 publications
(281 citation statements)
references
References 60 publications
6
274
1
Order By: Relevance
“…On the other hand, on-site point measurements are crucial to estimate the quality of the satellite-based BMB estimates, which are uncertain in their magnitude. Second, this sub-kilometre variability in ice-ocean processes poses challenges for coupling ice flow with ocean models, because highly resolved ocean models and community efforts, such as the Marine Ice Sheet-Ocean Model Intercomparison Project (MISOMIP), are typically gridded with 1-2 km (Dinniman et al, 2016;Asay-Davis et al, 2016). This is too coarse to capture the spatial variability that we observe here.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, on-site point measurements are crucial to estimate the quality of the satellite-based BMB estimates, which are uncertain in their magnitude. Second, this sub-kilometre variability in ice-ocean processes poses challenges for coupling ice flow with ocean models, because highly resolved ocean models and community efforts, such as the Marine Ice Sheet-Ocean Model Intercomparison Project (MISOMIP), are typically gridded with 1-2 km (Dinniman et al, 2016;Asay-Davis et al, 2016). This is too coarse to capture the spatial variability that we observe here.…”
Section: Discussionmentioning
confidence: 99%
“…(9) and the Coulomb friction law Eq. (16) can be combined (Tsai et al, 2015;Asay-Davis et al, 2016) by taking the lowest friction value of both. Since at the grounding-line basal sliding velocities are considered highest, this equally implies high basal drag in a traditional power-law sliding law.…”
Section: Coulomb Friction Lawmentioning
confidence: 99%
“…Unless an ice stream has exceptionally strong lateral buttressing (Robel et al, 2016), a marine ice sheet instability, once started, may only be stopped by modifying bathymetry to provide extra buttressing, as simulated by flow-band modeling on Thwaites Glacier (Wolovick and Moore, 2018). However, initial results from the BISICLES model evaluating the response of an idealized vulnerable marine glacier to imposed warming found that returning the entire water column to cooler conditions reversed the retreat that had begun during the warming (Asay-Davis et al, 2016). It seems reasonable to expect that solar geoengineering, like emissions cuts, may help to prevent other marine glaciers from becoming unstable by limiting surface melt that could lead to ice shelf collapse but would have a limited ability to reverse subsurface warming on decadal timescales.…”
Section: Ice Shelf Collapse and Dynamic Mass Lossmentioning
confidence: 99%